(untitled) (Baghdad Science Journal, 2024)
This study aimed to detect the relation of Heme oxygenase-1(HO-1) and Glutathione-S-transferase (GST) in obese patients, against oxidative stress. The study included 139 samples of people with age range of 35-65 years divided in two groups according gender (female and male) groups while four gropes according body mass index (BMI). Blood samples were collected from AL-Yarmouk Hospital at the period between September/2022 to January/2023. Some biochemical parameters were measured for all study groups, which include: -determination of serum HO-1 levels by using the ELISA-technique, lipid profile, GST activity, and fasting serum glucose (FSG) assessed manual. The BMI, waist hip ratio(WHR) and low density lipoprotein (LDL) were found to be significant [(38.83±0.44b) (32.03±0.26a) (26.40±0.22d) (23.10±0.28c)], [(1.01±0.03b) (0.92±0.02ab) (0.93±0.01ab) (0.88±0.01a)] ,[(80,42±7.47a) (99.74±6.63ab) (112.93±10.12b) (83.94±8.95ab)] respectively and not significant with other parameters of lipid profile, FSG, and Atherogenic index. Also, it appeared that the HO-1 levels were higher in obese groups compared with healthy groups [(2.06 ± 0.09b)(1.95 ± 0.04ab) (1.88 ± 0.04ab)(1.75 ± 0.05a)] ng/ml respectively . It was shown that the increasing of GST level in healthy compared with obese groups [(6.10± 0.57c)(4.120 ± 0.69b)(2.44 ± 0.21a)(2.71± 0.30ab)]IU/L respectively .The result showed that the increase in BMI,WHR and HO-1 in obese female and BMI,TG,HO-1 and VLDL in obese male ,compared with female and male healthy groups ,while the results showed an increase in GST levels in healthy female and male groups .We conclude from this study that high levels of heme oxygen-1 synchronized with low of glutathione-S- transferase , clearly indicating their primary role in detoxification, protection of the against oxidative stress, and prevention of the development of metabolic diseases.